Weight maintenance as a tight rope walk - a Grounded Theory study - Weinehall Lars; Larsson Christel; Lindvall Kristina; Emmelin Maria (BMC, 2010)
Abstract Background Overweight and obesity are considerable public health problems internationally as well as in Sweden. The long-term results of obesity treatment are modest as reported by other studies. The importance of extending the focus to not only comprise obesity treatment but also prevention of weight gain is therefore being emphasized. However, despite the suggested change in focus there is still no consensus on how to prevent obesity or maintain weight. This study reports findings from a qualitative study focusing on attitudes, behaviors and strategies important for primary weight maintenance in a middle-aged population. Methods In depth interviews were conducted with 23 maintainers and four slight gainers in Sweden. The interviews were transcribed and an analysis of weight maintenance was performed using Grounded Theory. Results Based on the informants' stories, describing attitudes, behaviors and strategies of importance for primary weight maintenance, a model illustrating the main findings, was constructed. Weight maintenance was seen as "a tightrope walk" and four strategies of significance for this "tightrope walk" were described as "to rely on heritage", "to find the joy", "to find the routine" and "to be in control". Eleven "ideal types" were included in the model to illustrate different ways of relating to the main strategies. These "ideal types" described more specific attitudes and behaviors such as; eating food that is both tasteful and nutritious, and choosing exercise that provides joy. However, other somewhat contradictory behaviors were also found such as; only eating nutritious food regardless of taste, and being physically active to control stress and emotions. Conclusion This study show great variety with regards to attitudes, strategies and behaviors important for weight maintenance, and considerations need to be taken before putting the model into practice. However, the results from this study can be used within primary health care by enhancing the understanding of how people differ in their relation to food and physical activity. It informs health personnel about the need to differentiate advices related to body weight, not only to different sub-groups of individuals aiming at losing weight but also to sub-groups of primary weight maintainers aiming at maintaining weight.